Trends and Determinants of Osteoporosis Treatment and Screening in Patients With Rheumatoid Arthritis Compared to Osteoarthritis - (:unkn) unknown (WILEY, 2018)
Objective. To profile osteoporosis (OP) care in patients with rheumatoid arthritis (RA) over the past decade. Methods. Patients with RA or osteoarthritis (OA) were followed from 2003 through 2014. OP care was defined as receipt of OP treatment (with the exception of calcium/vitamin D) or screening (OPTS). Adjusted trends over followup, and the factors associated with OP care, were examined using multivariable Cox proportional hazards. Results. OPTS was reported in 67.4% of 11,669 RA patients and in 64.6% of 2,829 OA patients during a median (interquartile range) 5.5 (2-9) years of followup. In patients for whom treatment was recommended by the 2010 American College of Rheumatology (ACR) glucocorticoid-induced OP (GIOP) guidelines (48.4% of RA patients and 17.6% of OA patients), approximately 55% overall reported OP medication use. RA patients were not more likely to undergo OPTS compared to OA patients (hazard ratio 1.04 [95% confidence interval 0.94-1.15]). Adjusted models showed a stable trend for OPTS between 2004 and 2008 compared to 2003, with a significant downward trend after 2008 in both RA and OA patients. Factors associated with receipt of OP care in RA patients were older age, postmenopausal state, prior fragility fracture or diagnosis of OP, any duration of glucocorticoid treatment, and use of biologic agents. Conclusion. Approximately half of RA patients for whom treatment was indicated never received an OP medication. OP care in RA patients was not better than in OA patients, and the relative risk of the application of this care has been decreasing in RA and OA patients since 2008 without improvement after the release of the 2010 ACR GIOP guideline.
Keywords: UNITED-STATES; PREVENTION; FRACTURE; WOMEN; MANAGEMENT; CARE; THERAPY; RISK; MEN; DISPARITIES